2019
DOI: 10.1177/1354816619844368
|View full text |Cite
|
Sign up to set email alerts
|

Smart tourists as a profiling market segment: Implications for DMOs

Abstract: The concept of smart tourism has gained a significant attention in the last years, leading to fruitful discussions among scientists and practitioners; however, there has been lack of attention paid to smart tourists so far. Although this emerging type of tourist has been conceptualized, it is now important to find whether it can be considered as a market segment. The article fills the gap in the smart tourism research by using two-step cluster analysis to classify 5975 tourists, finding a smart tourism market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 95 publications
(112 reference statements)
1
23
0
6
Order By: Relevance
“…Our study's findings indicate that all three stages (and the post-consumption experience) are equally significant. Furthermore, it was found that all stages are significant, confirming that this ST technology could be influential in adopting a sustainable and responsible behavior by smart tourists, beneficial to the appropriate management of tourism destinations, as suggested by previous studies [2,9,23,31,37,52]. By having a responsible behavior, smart tourists as the main actors of the ST paradigm could make a significant contribution to sustainable management of tourism resources and assets.…”
Section: Reliability and Validity Testingsupporting
confidence: 66%
See 4 more Smart Citations
“…Our study's findings indicate that all three stages (and the post-consumption experience) are equally significant. Furthermore, it was found that all stages are significant, confirming that this ST technology could be influential in adopting a sustainable and responsible behavior by smart tourists, beneficial to the appropriate management of tourism destinations, as suggested by previous studies [2,9,23,31,37,52]. By having a responsible behavior, smart tourists as the main actors of the ST paradigm could make a significant contribution to sustainable management of tourism resources and assets.…”
Section: Reliability and Validity Testingsupporting
confidence: 66%
“…It can be claimed that this ST technology can be influential in adopting a sustainable and responsible behavior in performing a set of anticipatory acts [1,2,32,37,52]. Hence, this study states the following hypothesis: Hypothesis 1.…”
Section: Research Framework and Hypothesesmentioning
confidence: 91%
See 3 more Smart Citations